DESIGN AND DEVELOPMENT OF CINEMATIC VIDEO BASED ON MUSIC VIDEO GAME “LEGEND OF ZELDA – OCARINA OF TIME” USING ADDIE METHOD - Jerremy Alexander; Tony Wibowo (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Technology has been advantages in these recent years, they are easy to use and fast, especially when it comes for media like video games. Digital geography is now a major and very widespread interest. In human geography, there are two main theoretical approaches to video games. The first has considered the representational strategies and politics of video games: how video games depict the world, and the ethics of that depiction, the second is looking at the representational approach as a poor place to capture the contingencies of the digital world, and the embodied interactions between games and gamers. Based on discussion that has been discussed, we will design and develop a cinematic video, the design is that we will make a cinematic video using background music from a video game called "Legend of Zelda - Ocarina of Time", the applications used to make the video are Adobe Premiere Pro CC and Adobe After Effects CC, we will combine several gameplay clips from other games and then the writer will combine them with some of game soundtracks from "Legend of Zelda - Ocarina of Time" which will resulting a cinematic video, and we also added a Japanese poetry called haiku for the video storyline, and when it is finished, we will upload the video result to YouTube.